Examining the Islamic stock market efficiency: Evidence from nonlinear ESTAR unit root tests - Setianto, Rahmat Heru; Manap, Turkhan Ali Abdul (The Indonesian Capital Market Review, 2015)
This paper empirically examines the efficient market hypothesis (EMH) in the Islamic stock market namely Jakarta Islamic Index by emphasizing on the random walk behavior and nonlinearity. In the first step, we employ Brock et al. (1996) test to examine the presence of nonlinear behavior in Jakarta Islamic Index. The evidence of nonlinear behavior in the indices, motivate us to use nonlinear ESTAR unit root test procedure recently developed by Kapetanios et al. (2003) and Kruse (2011). The nonlinear unit root test procedure fail to rejects the null hypothesis of unit root for the indices, suggesting that Jakarta Islamic Index characterized by random walk process supporting the theory of efficient market hypothesis. In addition, Lumsdaine and Papel (LP) test identified significant structural breaks in the index series.